Video Promosi Wisata Pantai Maligi Pasaman Barat - Nursholeha, Anisa; Annisa, Syerlie (TSAQOFAH, 2025)
West Sumatra is a region rich in natural, cultural, and religious tourism potential, distributed across various regencies and cities. One area with significant yet underdeveloped tourism potential is Maligi Village, located in Sasak Ranah Pasisia District, West Pasaman Regency. Since its designation as a tourism village by the Regent's Decree in 2019, the destination has been managed by the Tourism Awareness Group (Pokdarwis) under the initiative of the Maligi Tourism Care Movement (GERMALISTA). The village’s main attraction is Pantai Maligi, renowned for its distinctive western Sumatra coastal landscape. However, tourism promotion efforts remain limited, particularly in terms of digital information updates and the quality of available visual media. Existing promotional videos do not yet meet cinematographic standards capable of effectively capturing tourist interest. This study aims to design a tourism promotional video that is both communicative and engaging, showcasing not only the natural beauty of Pantai Maligi but also highlighting local culture, such as traditional pedati transportation and the preparation of signature cuisine like rendang tiram. The resulting video is expected to strengthen local identity and enhance the competitiveness of the destination at both regional and national levels.